OROLBOʻYI MINTAQASIDA EKOSHAHARNI LOYIHALASH TAMOYILLARI (KIUT Publication, 2025)
The process of urbanization is becoming one of the main driving forces of environmental change today. Cities are growing at an incredible rate, which leads to the expansion of infrastructure and the reduction of natural areas. One of the main tasks of modern urban planning is to find a balance between the development of the city and the preservation of natural ecosystems. In the context of global environmental problems, nature conservation in urban areas plays an important role not only in preserving biodiversity, but also in maintaining the quality of life of urban residents. The article is devoted to the formation of ecological urban planning in the Aral Sea region of the Republic of Karakalpakstan, and the purpose of the study is to design cities in these areas with extreme conditions. The threat of an ecological catastrophe of the Aral Sea leads to the emergence of a new urban form - ecological cities, and the issue "Ecological urban planning solutions in the city of Muynak in the Aral Sea region" presents ecological urban planning solutions for a specific city and a specific planning situation. Here, a general plan, detailed planning solutions, ecological architectural and construction solutions were developed in accordance with scientific and design requirements, especially for the city of Muynak, taking into account the requirements of ecological urban development. The experience of foreign and domestic countries in designing cities located in regions with difficult natural and climatic conditions was also summarized.